One woman orchestra: análisis funcional del formato de interpretación live looping, basado en los casos de KT Tunstall, Ed Sheeran y Kimbra, aplicado en un recital final - Chiriboga Salguero, Esther Andrea (2017)
This document presents a series of musical subjects that have been audibly analyzed in their compositions and performance, using live looping as their main tool. This method has been known as innovative in the Ecuadorian musical market, because of the use of electronic music tools inside an acoustic format. A research about analogue and digital loops has been done. Also a study about Terry Riley as a pioneer of this method during the decade of the 60’s has been written. Likewise, a detailed analysis upon: Ed Sheeran, KT Tunstall, and Kimbra, has been made. These are current artists who perform with live looping. Written and practical transcripts have been developed with this information as well as detailed process of these. Additionally to this, visual maps of the use of the loopers in each song have been included. This paper is enthusiastic with the hypothesis of having more musical groups and projects in Ecuador that perform in a format where technology is the main character, but without losing the analogue essence. The line of research is performance. Therefore, the findings of the study were applied in the performance of a final concert. This showed the use of loopers applied to a vocal and instrumental performance in three different formats: vocal, vocal-instrumentalist, and band. The repertoire is attached to the end of this document. This document reveals that the application of loopers is practical and usable in diverse instrumental formats, and hopes that many more musicians are motivated to use them in their compositions and performances.